EFFECTIVENESS OF LAVENDER AROMATHERAPY ON SLEEP QUALITY AND ANXIETY IN PATIENTS WHO UNDERGOING HEMODIALYSIS - Setyaningrum, Niken; Setyawan, Aris (International Journal of Islamic and Complementary Medicine, 2023)
Hemodialysis is a long-term therapy that must be done by patients with chronic kidney disease. Patients who undergo therapy for a very long time will have an impact on the patient's psychology. Psychological impacts are anxiety and sleep disturbances. Anxiety that is constantly felt by the patient and accompanied by poor sleep quality can cause changes in the physiological, endocrine system, cardiovascular system, immune system and nervous system. To overcome sleep disorders and anxiety in hemodialysis patients, non-pharmacological options can be used, namely Lavender Aromatherapy through inhalation. The purpose of this study was to determine the effect of Lavender Essential Oil Aromatherapy on Sleep Quality and Anxiety in Hemodialysis Patients. The study was conducted on 32 hemodialysis patients. The intervention was carried out for 3 times of administration during intra hemodialysis. The instruments used were the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality and The Zung-Self Rating Anxiety Scale (ZSAS) to measure anxiety which was applied before and before the test. Analysis of test data using one sample t test for both variables partially showed that the difference in the average score of sleep quality and anxiety with each p value of 0.000 means that there is an increase in sleep quality and a decrease in anxiety levels in patients undergoing hemodialysis in the intervention group. Lavender aromatherapy can be applied as an enhanced intervention to treat sleep disorder and is effective in patients undergoing hemodialysis.